Na poti v bolonjsko reformo - razmislek o kakovosti in vlogi upravljanja človeških virov v visokem šolstvu - Nadoh Bergoč, Jana (Družboslovne razprave, 2007)
The authors discuss the concept of the quality of higher education which is, at a time when Europe faces tendencies to harmonise the European higher education area, particularly topical. There have been considerable deviations in perspectives on how to improve the quality of higher education since the 1980s, when the concept was implemented in Europe, until the present. At the forefront of the article lies the concept of quality as a transformation, which implies the learner as an autonomous subject. In this context, teachers are stimulated to use more contemporary pedagogical tools and to take an active role in the development of critical thinking and empowerment of learners. Simultaneously they are obliged to search for adequate ways of implementing the Bologna process. In this process the role of management, especially human resource management in higher education institutions, is crucial. Nevertheless, this discipline is still not emphasised enough within the higher education management processes. The majority of changes in the area of quality improvement are concentrated on the identification of measures, indexes and standards of quality to help higher education institutions satisfy the goals of the Bologna reform and other similar tensions. This is reflected in Slovenia as well as in the European higher education area.
Keywords: University education system; Visoko šolstvo; Education; Izobraževanje; Kakovost; Quality; Upravljanje s človeškimi viri; Human resource management; Institucije; Institutions; kvaliteta; upravljanje človeških virov; Bologna Process; bolonjska reforma